PENERAPAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) BERBANTUAN MEDIA BUKU CERITA BERGAMBAR UNTUK MENINGKATKAN LITERASI MEMBACA PESERTA DIDIK SD MUHAMMADIYAH 8 SURABAYA - Dewi Setianingsih; Lina Listiana; Dyah Eka Sulistyorini (Universitas Muhammadiyah Surabaya, 2024)
This research aims to describe the application of the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by illustrated storybook media to improve the reading literacy of class III students at SD Muhammadiyah 8 Surabaya. This type of research is pre-experimental with a one-group pretest-posttest design. The research method is descriptive. The research population was 63 grade III students at SD Muhammadiyah 8 Surabaya. The sampling technique used purposive sampling with a sample of 19 class IIIB students. Data collection techniques are tests, observation, questionnaires and document review. Data collection instruments are test sheets, observation sheets, questionnaire sheets, written documents and recorded documents. The data analysis technique uses descriptive analysis. The conclusions of the research are: (1) Application of the CIRC learning model can increase students' reading literacy; (2) The application of the CIRC model assisted by illustrated story book media can increase interest in reading and ultimately improve student learning outcomes in Indonesian language learning.